Comparison of the Effectiveness of Logotherapy and Group Compassion-Focused Therapy on Distress Tolerance in Patients Undergoing Knee Joint Surgery with a Three-Month Follow-Up - Arab, Maryam; Amirfakhraei, Azita; Zarei, Eghbal (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness of logotherapy and group compassion-focused therapy on distress tolerance among patients undergoing knee joint surgery with a three-month follow-up period. Methods and Materials: This study employed a quantitative quasi-experimental design using a pretest–posttest and follow-up format with a non-equivalent control group. The statistical population included all patients undergoing knee joint surgery who referred to treatment clinics in Semnan during the second half of 2024. Based on G*Power analysis, 45 participants were selected through convenience sampling and randomly assigned to three groups: logotherapy (n = 15), compassion-focused therapy (n = 15), and control (n = 15). Data were collected using the Distress Tolerance Scale developed by Simmons and Gaher (2005). The experimental groups participated in eight weekly sessions of logotherapy based on the approach of Viktor Frankl (1978) and compassion-focused therapy based on the model of Kristin Neff and Christopher Germer (2016). Data were analyzed using repeated measures analysis of covariance and Bonferroni post hoc tests in SPSS-26. Findings: The findings revealed that both logotherapy and group compassion-focused therapy significantly improved distress tolerance compared with the control group at posttest and follow-up stages (p < .05). Analysis of covariance demonstrated a significant effect of group membership on distress tolerance at posttest (F = 72.03, p < .001, η² = .735) and follow-up (F = 71.116, p < .001, η² = .752). Bonferroni post hoc comparisons further indicated that the logotherapy group achieved significantly higher distress tolerance scores than the compassion-focused therapy and control groups, while the compassion-focused therapy group also outperformed the control group. The intervention effects remained stable during the three-month follow-up period. Conclusion: The findings suggest that both logotherapy and compassion-focused therapy are effective psychological interventions for improving distress tolerance among patients undergoing knee joint surgery.